Morphology, molecular characterisation and systematic position of the genus Cynura Cobb, 1920 (Nematoda: Plectida - Holovachov, O.; Boström, S.; Tandingan De Ley, I.; Robinson, C.; Mundo-Ocampo, M; Nadler, S. A. (Nematology, 2013)
Descriptions of three known species of Cynura, i.e., C. cerambus, C. klunderi and C. papillata, are given, including SEM micrographs of C. cerambus and a tabular compendium for all species of the genus. The phylogenetic relationships of C. klunderi are inferred from molecular data. Bayesian analyses of small subunit (SSU) of rRNA sequences support a position nested among the Plectidae suggesting the secondary simplification in the morphology of pharyngeal valvular apparatus in Cynura and the ‘return’ from a terrestrial to a marine environment in this genus.